Analisis Break Even Point (BEP) Pada UMKM Javadwipa_Roastery Dan Kedai Kopi Di Masa Pendemi - Dani Susanto; Nur Azizah; Ribangun Bamban Jakaria (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The coffee business, especially during the pandemic, faces challenges in maintaining operations and ensuring profitability. This study focuses on Javadwipa_roastery & Coffee Shop, exploring its Break Even Point (BEP) to assess financial sustainability. Through direct observation and interviews, data on fixed and variable costs were collected. Findings revealed monthly fixed costs of Rp. 1,000,000, and variable costs including raw materials, equipment, labor, and transportation, totaling Rp. 7,223,500. The BEP analysis for Cappuccino and Matcha Latte showed unit BEP at 468.33 and 200.71 respectively, with corresponding Rp. BEP at Rp. 3,275,058.28 and Rp. 3,008,565.31. Understanding BEP aids in strategic planning and decision-making, crucial for achieving optimal profitability in the coffee business.